Utilising Polyethylene Terephthalate (Pet) as Green Materials in Concrete - SHIVANESSWARY; Syed Mohd Fareed; WAN AMIZAH (Progress in Engineering Application and Technology, 2025)
The rising accumulation of plastic waste, particularly Polyethylene Terephthalate (PET), poses a significant environmental challenge due to its non-biodegradability and contribution to greenhouse gas emissions. This research explores the feasibility and effectiveness of incorporating PET as a sustainable additive in concrete mixes to enhance performance and promote environmental sustainability. The study aims to determine the optimal PET content and its effect on the mechanical, physical, and thermal properties of concrete. Five mix designs were prepared with PET contents of 0%, 0.5%, 1%, 1.5%, and 2% by total volume. Laboratory tests were conducted by British Standards (BS) to evaluate compressive strength, split tensile strength, water absorption, and thermal conductivity. The results indicated that the mix with a range of 0.5% to 1% PET achieved the best balance between mechanical strength and thermal insulation. The study concludes that incorporating PET at a range of 0.5% to 1.0% PET by volume in concrete is technically viable for non-structural and thermally efficient applications. It is recommended to explore surface treatments or hybrid materials to mitigate moisture ingress at higher PET contents. The findings support sustainable construction practices and contribute to circular economy efforts by valorising plastic waste into functional building materials.